0015 Manipulating Body Temperature: Effects on Sleep in Postmenopausal Women. (27th May 2020) - Reid, K J; Kräuchi, K; Grimaldi, D; Sbarboro, J; Attarian, H; Zee, P C
Abstract: Introduction: A decline in sleep quality and reduction in slow wave sleep (SWS) and slow wave activity (SWA) are common in older adults. Prior studies have shown that manipulating body temperature during sleep can increase SWS/SWA. The aim of this study was to determine the effects of manipulation of body temperatures during sleep, using a high heat capacity mattress, on SWS/SWA and heart rate variability in post-menopausal women. Methods: Twenty-four healthy postmenopausal women between 40–75 years of age (mean age 62.4 ± 8.2 years, mean BMI 25.4 ± 3.5 kg/m 2 ) were randomized in a single-blind, counterbalanced, cross-over manner to sleep on either a high heat capacity mattress (HHCM) or a low heat capacity mattress(LHCM) a week apart. Sleep was recorded using polysomnography during an 8-hour sleep opportunity. Core and peripheral temperatures were recorded using Equivital and ibutton respectively. Results: In comparison to the LHCM, sleep on HHCM exhibited a selective increase in SWS (average increase in Stage N3 of 9.6 minutes (2.1%), p = 0.04) and in slow oscillatory activity (0.5-1Hz) in the first NREM/REM cycle (p=0.04). In addition, the HHCM induced a greater reduction in core body temperature (p=0.002), and delayed the increase in mattress surface temperature (maximal difference LHCM-HHCM: 4.66±0.17°C). Average heart rate was 2.7 beats/minute lower across the night on the HHCM compared to the LHCM (p=0.001). Conclusion: The results of this study indicate that manipulation of body temperature during sleep may be a useful approach to enhance SWS sleep and cardiovascular function in postmenopausal women. Support: Technogel